Signatures for Sale : How Nominee Services for Shell Companies are Abused to Conceal Beneficial Owners - Nielson, Daniel Lafayette (Washington, DC: World Bank, 2022)
This report analyzes a family of related corporate arrangements in which nominees act as agents of principals in control of shell companies. It focuses on how nominee arrangements can be abused to facilitate financial crime by obscuring the identity of those in control of shell companies and on policies designed to counter such abuses. The report draws evidence from a global mystery shopping exercise based on thousands of solicitations for shell companies, as well as marketing information from shell company providers, and journalistic and policy research on the topic. Nominee arrangements are currently both a threat and a missed opportunity for policy makers. Such arrangements are critical to corporate beneficial ownership transparency as a major but underappreciated point of vulnerability. Strengthening the regulation of nominee arrangements can enhance the transparency of shell companies and help reduce financial crime. Taking best advantage of this opportunity requires greater attention to the transparency of nominee arrangements, better practical enforcement of rules, and replacement of a single country-by-country approach in national evaluations with a more multijurisdictional perspective.